Role of electricity generation technology in the long-term energy sustainability of India - Aqsa Anjum; Jahangir Chauhan (The Holistic Approach to Environment, 2024)
Electricity distribution has become one of the most essential components of our society since the beginning of human civilization, relying on an abundant, reliable, and affordable power supply. Fossil fuels dominate the production of electricity (89.57 %), emitting 68.7 % of greenhouse gases, polluting water and soil, and depleting fossil fuels. Future energy needs are faced with growing demand for coal (772 million tonnes by 2040) and fluctuating fuel prices. The Indian power sector withdraws over 20 billion m3 of water, whereby coal power plants use around 35 % of freshwater. Among the seventeen sustainable development goals, Goal 7 emphasizes meeting the demand for electricity, the availability of clean fuels, and mitigating air pollution. In 2021, about 747 TWh of energy consumption was met by coal, oil (92 TWh), and solar energy (25 TWh). Renewable power would meet the world’s growing energy needs, reduce greenhouse gas emissions, boost the economy, and strengthen the society. Therefore, renewable energy has gained global attention as a sustainable electricity source. For this, a thorough examination of the economic and social implications of electricity generation technologies must be carried out. This study discusses how fossil fuel-based electricity generation affects global health and the environment and helps achieve Goal 7 of the sustainable development goals. All sectors must work together to stop global warming and water war and make electricity available worldwide for integrated development.